Winn L. Rosch hardware bible. - Rosch, Winn L. (Que Pub., 2003)
The Winn L. Rosch Hardware Bible provides a background on how things work, puts competing technologies, standards, and products in perspective, and serves as a reference that provides quick answers for common computer and technology questions. It functions as a buying guide, telling not only what to buy, but why. It also lays the foundation for upgrading or repairing a computer, but stops short of the step-by-step mechanics of the process. The chief purpose of the Hardware Bible remains educational. Some new features in this edition include rewritable DVD technology as well as Blu-ray Discs, wireless networking including 802.11a and 802.11b, Bluetooth wireless communications, and extended coverage of digital cameras, scanners, and telecommunications...and much more!